Exploring Needs and Quality of Life of Forensic Psychiatric Inpatients in the Reformed Italian System, Implications for Care and Safety - Vorstenbosch, Ellen; Castelletti, Luca (Frontiers in Psychiatry, 2020)
The Italian forensic psychiatric system underwent drastic reforms. The newly developed facilities are inspired by psychiatric community services, embracing a recovery-oriented approach. Needs and quality of life are broader concepts that consider the more rehabilitative and humanitarian aspects of treatment. In one of the new Italian forensic psychiatric services, this cross-sectional study aimed to investigate the needs and quality of life of forensic psychiatric patients. A second aim was to validate the Italian version of the Forensic inpatient Quality of Life questionnaire Short Version (FQL-SV). Overall, 42 forensic psychiatric patients were assessed using the Forensic version of the Camberwell Assessment of Need (CANFOR), the Historical-Clinical-Risk-Management-20 (HCR-20), the FQL-SV and the World Health Organization Quality of Life (WHOQoL-Bref). Patients reported significantly fewer needs, whether met or unmet, than their treating clinicians. The general level of agreement between patients and clinicians on specific needs was low: Kappa values were <.40 for 64% of the total needs and 46% of the unmet needs. Risk factors according to the HCR-20 mean scores were 13.1, 4.6 and 6.4 for the historical, clinical and risk management subscale. Quality of life was moderate to high for 74% of the patients. Our results showed that lower numbers of needs, whether reported by patients or clinicians, were associated with a better quality of life. The Italian FQL-SV had a Cronbach’s alpha of 0.86 and correlated as expected with the WHOQoL-Bref. The FQL-SV is a valid and reliable tool, justifying its use for routinely assessing QoL in Italian forensic psychiatric services. This study enhances our understanding of needs and quality of life of forensic psychiatric patients and how their assessment could have an additional value for recovery-oriented treatment in forensic psychiatry. Although the detained status of forensic patients imposes real limits on the capacity for autonomy and choice, incorporating the patient's perspective on decision-making processes, in relation to aspects of treatment, care, and daily life, may have benefits such as a better treatment adherence or therapeutic alliance. Future research should clarify how routinely assessing needs and quality of life can contribute to the recovery of these forensic psychiatric patients.